Adenosine 5′-monophosphate-activated protein kinase ameliorates bovine adipocyte oxidative stress by inducing antioxidant responses and autophagy - Xu, Qiushi; Fan, Yunhui; Loor, Juan J.; Liang, Yusheng; Sun, Xudong; Jia, Hongdou; Zhao, Chenxu; Xu, Chuang (Journal of dairy science, 2021)
Adipose tissue concentration of reactive oxygen species (ROS) increases in dairy cows with ketosis, suggesting that the tissue experiences oxidative stress. Autophagy, an adaptive response to cellular stress, has been shown to promote survival and plays a critical role in antioxidant responses. Dysregulation of adenosine 5′-monophosphate-activated protein kinase (AMPK) is closely related to antioxidant responses and autophagy of adipocytes in animal models of metabolic disorders, but its role in bovine adipose tissue during periods of stress is unknown. We hypothesized that AMPK may play important roles in the regulation of oxidative stress in adipose tissue of ketotic cows. Specific objectives were to evaluate autophagy status and AMPK activity in adipose tissue of ketotic cows, and their link with oxidative stress in isolated bovine adipocytes. Selection of 15 healthy and 15 clinically ketotic Holstein cows at 17 (±4) d postpartum was performed after a thorough veterinary evaluation for clinical symptoms and also based on serum β-hydroxybutyrate concentrations before collection of subcutaneous adipose tissue samples. Primary cultures of bovine adipocytes isolated from the harvested adipose tissue were stimulated with varying concentrations of H2O2 (0, 50, 100, 200, or 400 μM) for 2 h. In another experiment, adipocytes were cultured with the AMPK activator A769662 or adenovirus-containing small interfering RNA (ad-AMPKα-siRNA) for 3 or 48 h, respectively, followed by H2O2 exposure (200 μM) for 2 h. Compared with healthy cows, clinical ketosis led to increased abundance of AMPK and nuclear factor erythroid-derived 2-like 2 (NFE2L2), but lower abundance of Kelch-like ECH-associated protein 1 (KEAP1) in adipose tissue. Abundance of the key proautophagy proteins Beclin1, sequestosome 1 (SQSTM1), autophagy-related gene 7 (ATG7), ATG5, and ratio of microtubule-associated protein light chain 3 (LC3) II to LC3I were greater in adipose tissue of ketotic cows. In bovine adipocytes, treatment with H2O2 induced accumulation of ROS and malondialdehyde (MDA), whereas H2O2 stimulation inhibited activities of the antioxidant enzymes glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD). Addition of AMPK activator A769662 increased antioxidant response via activating NFE2L2 and its downstream targets heme oxygenase 1 (HMOX1), superoxide dismutase 1 (SOD1), catalase (CAT), and glutathione-S-transferase (GST) to improve H2O2-induced oxidative stress in adipocytes. Simultaneously, activation of AMPK increased abundance of Beclin1, SQSTM1, ATG7, ATG5, and ratio of LC3II to LC3I. In contrast, inhibition of AMPK downregulated abundance of NFE2L2, HMOX1, SOD1, CAT, Beclin1, SQSTM1, ATG7, ATG5, and ratio of LC3II to LC3I, and further aggravated H2O2-induced oxidative stress. Overall, these data indicate that activation of AMPK, as an adaptive mechanism for acute metabolic regulation of adipose tissue homeostasis, can induce antioxidant responses and autophagy, and further reduce oxidative stress in bovine adipocytes.